Monovalent antibodies directed to transformation-sensitive membrane components inhibit the process of viral transformation - Lingwood, C. A. (1978)
Monovalent antibodies (Fab) directed to two classes of transformation-sensitive cell surface components, ganglioside and galactoprotein a (Gap a), inhibit the process of oncogenic viral transformation of cells. Mouse 3T3 cells infected with murine sarcoma virus were not transformed in terms of morphology change and enhancement of sugar uptake when the infected cells were cultured in the presence of monovalent antibodies directed to GM(1) ganglioside or to Gap a. Transformation inhibitory activity of these cell surface ligands was not related to cell growth inhibition because the monovalent antibodies to globoside and divalent Con A were growth inhibitory but did not inhibit oncogenic transformation. Neither anti-GM(1) Fab nor anti-Gap a Fab inhibited virus production. The transformation inhibitory activity of antiganglioside and anti-Gap a Fab was additionally assessed by inhibiting the transformed phenotype in NRK cell lines with mutants of avian sarcoma virus that are temperature sensitive for expression of the transformation phenotype (NRK/LA25). In this cell line, the GM(3) ganglioside (not GM(1)) and Gap a were transformation-sensitive cell surface components. The expression at permissive temperature of transformed phenotypes, such as morphology change and capability of growth in 0.3% agar, was inhibited by preincubation of the cells with anti-GM(3) Fab or anti-Gap a Fab. GM(3) labeling of NRK/LA25 cells decreased at permissive temperature, whereas preincubation of cells with anti-Gap a, which induces the inhibition of transformation after a temperature shift, prevented the decline of GM(3) label on the cell surface. The data suggest a possible correlation between GM(3) and Gap a expression. Application of monovalent antibodies to these transformation-sensitive components may prevent changes of these components on cell surfaces, and thus may result in abortion of phenotypic expression of transformation, although the transforming gene (src) has been set active. These results indicate that pericellular structures influence gene expression.